Association between anxiety levels and hypertension among older adults - Nisa Fajriah; Dedi Wahyudin (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: As individuals age, older adults experience significant physiological decline, including reduced vascular elasticity, which contributes to the high prevalence of cardiovascular diseases. Biologically, persistent anxiety triggers the release of stress hormones, such as catecholamines and cortisol, which increase sympathetic nervous system activity and subsequently elevate blood pressure. Purpose: To examine the association between anxiety levels and hypertension among older adults. Method: This study employed a correlational research design with a cross-sectional approach. A total of 313 older adults from Cimanggu Village were recruited using a cluster random sampling technique. Data were collected using a structured closed-ended questionnaire that had been tested for validity and reliability. Bivariate analysis was performed using the Chi-square test. Results: Most respondents experienced severe anxiety (203; 64.9%). Furthermore, hypertension was identified in 195 respondents (62.3%). A statistically significant relationship was found between anxiety levels and the incidence of hypertension among older adults (p < 0.05). Conclusion: Anxiety levels were significantly associated with hypertension among older adults. These findings suggest that hypertension management in older adults should adopt a comprehensive approach that addresses both physical and psychological aspects of health.